Additive Technologies in Restoring the Functionality of Mobile Robots - Dawid TOMICA (dawid.tomica@wat.edu.pl); Lucjan ŚNIEŻEK (lucjan.sniezek@wat.edu.pl); Arkadiusz RUBIEC (arkadiusz.rubiec@wat.edu.pl) (Problemy Mechatroniki)
The study analyses challenges faced by robots used by EOD subunits, their working conditions, and possible damage during operations. The literature review takes into account long-term and incidental loads on the undercarriage and drive systems, which affect the functionality and durability of these robots. Moreover, the limitations and advantages of additive technology in restoring the functionality of these machines were verified, taking into account the operational environment of EOD subunits.